Governance, accountability, and political legitimacy: who participates in the European parliament's committee hearings (ECON 2004–2014). Issue 4 (19th May 2022) - Coen, David; Katsaitis, Alexander
ABSTRACT: The Europeanization of economic and financial governance poses a legitimacy question for the European Parliament (EP). Drawing from theories on resource-exchange and institutional legitimacy, we argue that committee hearings allow the EP to demonstrate its relevance as a political authority. We test our argument, focusing on the Committee on Economic & Monetary Affairs (ECON). Through an unprecedented systematic analysis of its hearings; we provide a fine-grained identification of all participants across two legislatures (2004-2014). We observe a considerable shift in the use of hearings from the 6th to the 7th legislature, reflected in the increase of events and participants. While business interests retain a strong presence, the participants' composition changes substantially. Research organizations and EU-level executive bodies saw the largest increase. Conversely, national level executive bodies saw a decrease in participation. Theoretically, we examine an understudied area of European governance, while contributing to discussions on interest group access, agency accountability, and deliberative procedures.